Editorial - Neves, Pedro Soares (UXUC - User Experience and Urban Creativity, 2025)
This issue of UXUC Journal emerges from the discussions, encounters, and ongoing dialogues generated during the July 2025 activities of the Urban Creativity Conference, now in its 12th edition. Once again, the event exceeded organizational expectations, confirming its role as a dynamic platform where research, practice, and experimentation around urban space intersect. The 2025 edition marked an important milestone with the adoption of a fully hybrid format, combining online and in-person participation. This model broadened access and inclusivity while simultaneously reducing the environmental impact associated with air travel—an especially relevant gesture given the socio-environmental concerns that permeate contemporary urban debates. At the same time, the value of physical presence was evident: in-person participation fostered richer exchanges, informal conversations, and embodied experiences that remain essential to urban and spatial discourse.